Higher Resting-state BNST-CeA Connectivity is Associated with Greater Corrugator Supercilii Reactivity to Negatively Valenced Images - Pedersen, Walker S. (Neuroimage, 2019)
The bed nucleus of the stria terminalis (BNST) and central nucleus of the amygdala (CeA) are hypothesized to be the output nodes of the extended amygdala threat response, integrating multiple signals to coordinate the threat response via outputs to the hypothalamus and brainstem. The BNST and CeA are structurally and functionally connected, suggesting interactions between these regions may regulate how the response to provocation unfolds. However, the relationship between human BNSTC-eA connectivity and the behavioral response to affective stimuli is little understood. To investigate whether individual differences in BNST-CeA connectivity are related to the affective response to negatively valenced stimuli, we tested relations between resting-state BNST-CeA connectivity and both facial electromyographic (EMG) activity of the corrugator supercilii muscle and eyeblink startle magnitude during affective image presentation within the Refresher sample of the Midlife in the United States (MIDUS) study. We found that higher right BNST-CeA connectivity was associated with greater corrugator activity to negative, but not positive, images. There was a trend-level association between right BNST-CeA connectivity and trait negative affect. Eyeblink startle magnitude was not significantly related to BNST-CeA connectivity. These results suggest that functional interactions between BNST and CeA contribute to the behavioral response to negative emotional events.